A framework to enable microstructure-sensitive location-specific fatigue life analysis of components and connectivity to the product lifecycle. (December 2022) - Gopalakrishnan, Saikiran; Bandyopadhyay, Ritwik; Sangid, Michael D.
Highlights: Developed a framework for location-specific lifing of components. Provides data connectivity between geometry, material microstructures, performance. Demonstrated use case for dual microstructure heat treated turbine disk. Provides hierarchical simulation structure from component-level to crystal plasticity. Improved precision in identifying the minimum allowable fatigue life. Abstract: Traditionally, aerospace components are treated as monolithic structures during lifing analyses, wherein distinct microstructural information at individual locations is not necessarily considered. In components with gradient microstructures, the resulting material allowables are conservative and associated with large uncertainty bounds. To improve precision in the life estimates, a location-specific lifing framework is developed, which tracks manufacturing processes and retrieves microstructural information at distinct locations for use within a crystal plasticity fatigue life prediction model. A use case for the lifing of a dual microstructure heat treated turbine disk component is demonstrated near the bore (fine grains) and rim (coarse grains) regions. We employ the framework to access (a) the grain size statistics and (b) the macroscopic strain fields to inform precise boundary conditions for the crystal plasticity analysis. The proposed location-specific lifing framework presents new opportunities for simultaneously designing the component and tailoring the microstructures to meet the targeted performance.